Upgrading education architecture by redefining critique session in design studio - Utaberta, Nangkula; Hassanpour, Badiossadat; Handryant, Aisyah Nur; Che Ani, Adi Irfan (Elsevier, 2013)
Architecture education with apprenticeship based training method has existed from long time ago. This type of education was based of practice and imitation. But today according to the design issue and open ended problems it is changed to transmitting the concept and idea of design. In this educating system which is based on critique all the efforts are to increase student's self criticizing ability by continuous criticisms to able to manage their own projects. Design is one of the most complex types of problem solving that involves several aspects and components. Its cognitive processes and procedures should be transmitted to the students through lectures and critique sessions. The current model in studios is based on ancient model that must be redefined and be made clearer in order to improve both learning and teaching ways. There is no unreasonable action in the world and all are perusing a prominent target, especially in educating system that in fact it is the base of all forward steps in community around us. This paper analyses architectural studios in order to find the weak and strength points and also to identify procedures and tools that can be used to support the studio based pedagogy in architecture. First we take a look on what is going on in design studios and then by classifying the critique methods in different type of studios and explaining each will explore the reasons of dissatisfactions and at the end will give some suggestions to upgrade the existing system.